PENERAPAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI). UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IIIA SDN 9 DURI BARAT KECAMATAN MANDAU KABUPATEN BENGKALIS - br Harianja, Nurmauli; Alpusari, Mahmud; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This Research was conducted because of the  results a learning  of mathematical class IIIA SD Negeri 9 Duri Barat Kecamatan Mandau. From 35 students who reached  KKM about 20 people ( 57,14 %) and students who did not be completed 15 people ( 42,86 % ) with an average 65,45 .The purpose of this research to increase yields of learn math students IIIA SD Negeri 9 Duri Barat Kecamatan Mandau  by the application of math education realistic Indonesia. The results obtained by the average value of 65,45 basic score increased in the first cycle of 26,11 % to 81,28. In the second cycle the average value of student  also increased by 38,21 % to 89,08. On the basis of completeness score mathematics students only 57,14 %. After teachers implement setrategi math education realistic Indonesia ( PMRI) in the first cycle classical completeness  increased to 89,57 %, the second cycle of classical completeness obtained are increased to  increase to  97,14 %. Activities of teachers at the  first meeting  of 75,00 % to a category good. The second meeting  increased to 80,00 % to a category good. In the scond cycle increased to  85,00 % to a category is good.  At a meeting of the second meeting of the scond cycle, the activities of teachers increased to, 90,00 % to a category is good. Activities of  students in the first cycle  of the first meeting have presentase 70,00 % to a category good. In the second increased to 80,00 % to a category good. At  the first meeting of the scond cycle of   student activity increased to 80,00 % to a category good and at  the second meeting of the scond cycle increased again to 90,00 % to a category good. Thus can be concluded that the implementation of math education realistic Indonesia ( PMRI) to improve learning outcomes mathematics students  class IIIA SD Negeri 9 Duri Barat Kecamatan Mandau Key words: math education realistic Indonesia, study results mathematics